The Role of Probiotics in Depression Therapy: Current State of Knowledge and Therapeutic Perspectives - Cyrkler, Weronika; Robak, Jakub; Telega, Stanisław; Bollin, Paweł; Szymczak, Urszula; Lachór, Wojciech Wiesław; Solarz, Monika Barbara; Piekarska, Julia; Solarz, Justyna Maria; Wawrzyńców, Jakub Tomasz (Quality in Sport, 2025)
Depression is one of the most common mental disorders worldwide, leading to a significant reduction in quality of life and an increased risk of suicide. The pathogenesis of major depressive disorder (MDD) remains complex and not fully understood, involving neurotransmitter disturbances, excessive activation of the hypothalamic-pituitary-adrenal (HPA) axis, and reduced levels of brain-derived neurotrophic factor (BDNF). In recent years, an increasing number of studies have highlighted the role of gut microbiota and the gut-brain axis as key elements in the pathogenesis of depression. This review aimed to analyze the current evidence on the impact of probiotic supplementation on depressive symptoms. A PubMed database search was conducted, including randomized clinical trials, meta-analyses, and systematic reviews from the last five years. The results of the analyzed studies suggest that probiotics, particularly Lactobacillus and Bifidobacterium strains, may reduce depressive symptoms, regulate neurotransmitter levels, and decrease inflammation. However, the effectiveness of probiotic supplementation varied depending on the strain used, intervention duration, and the study population. Despite promising results, further research is needed to determine optimal probiotic therapy protocols in depression.